Squared Msplit Estimation in Deformation Analysis – 2D Geodetic Network Case Study - Pleterski, Žan (Geodetski vestnik, 2025)
Deformation analysis is a complex procedure where, based on several periodic geodetic measurements, displacements of points in the geodetic network are detected and determined. On this basis, movements and deformations of the built and natural environment are detected. The article discusses the Squared Msplit estimation, an extension of the maximum likelihood method, which is one of the procedures used in deformation analysis. The equations of the Squared Msplit estimation are derived and the method is presented on 2D geodetic network case study. The effectiveness of the presented method is compared with the results of other deformation analysis approaches performed with the same numerical example. The results obtained using the Squared Msplit estimation slightly differ from the simulated values, with the maximum discrepancy being 11.5 mm at unstable points and 10.4 mm at stable points, which are satisfactory results. T he findings indicate that the Squared Msplit estimation provides results comparable to other methods. Therefore, it is considered suitable for deformation analysis and can be regarded as one of the applicable procedures in this field.
Keywords: deformacijska analiza; deformation analysis; geodetic surveys; geodetska izmera; geodetske mreže; iterative process; iterativni postopek; kvadratna metoda Msplit; point displacement in the geodetic network; premiki točk; Squared Msplit estimation